MUSCULAÇÃO: ASPECTOS POSITIVOS PARA O EMAGRECIMENTO - Léo de Paiva Montenegro (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction: The bodybuilding has not been widely prescribed for weight loss programs. Obesity has reached increasing numbers and become a public health problem because of the physiological changes that leads to the disease state and generating greater risk of disease. Strength training is an exercise and can aid in weight loss process. Objective: Review the positive aspects of the practice of bodybuilding to aid slimming. Materials and Methods: We performed a literature narrative review being used studies related to bodybuilding, EPOC, weight loss, strength training, obesity. Articles were selected according to the subject and his contribution to the present study. Discussion: Some aspects such as body composition, energy expenditure, EPOC and autonomy, influence the level of physical activity and daily caloric expenditure, which may be a contributing factor in weight loss. The increase of muscle mass also increases the basal metabolic rate. The bodybuilding program and EPOC can increase caloric expenditure during and after practice program. Adaptations of bodybuilding program increase the autonomy of individuals, making them more active, reducing the state of inactivity. Conclusion: The practice of bodybuilding has many positives aids in weight loss and should be present in weight loss programs.